An approach to popular medicine in Ubrique (1996-1997) - Orestes Rodríguez Aguado (Universidad de Alicante, 2012)
The need to cure illness is inherent to evolution of human mankind. In its developmental process as a civilization, the means for this aim have accompanied the increasing knowledge in all areas of wisdom. As technique improved, ancient methods were forgotten or relegated by the emergent knowledge. Regarding Medicine, on the contrary, the essence of illness having not been known or accepted by healthy and sick has allowed techniques, remedies and methods to live through modern Medicine and be used nowadays. The chosen setting for this work is Ubrique, where 43 interviewed people have furnished us with information on disorders or health problems and useful remedies.